Social Networking Sites — Friend or Foe of Social Skills in Education - Meena; Kaur, Lavleen (JOURNAL OF INDIAN EDUCATION, 2013)
The social networking sites are gaining a lot of popularity as one of the modes of communication these days to remain socially active. Not only do these social sites bridge the social boundaries but they also provide a common platform to communicate and socialise in the offline social set up with other individuals. Social researchers are now baffled at its impact on user’s lives and their social life. Some fear that excessive use of Social Networking Sites might diminish human relationships and increase social isolation. Others opine that it will improve people’s social skills via networking. The present study tries to find that whether the usage of Social Networking Sites will be ‘friend’ or ‘foe’ of social skills in the education and how the role of teacher comes in between to guide the students in this regard. The major findings of study were: (i) there exist significant relationship between Social Networking Sites usage and Social Skills of the pupil teachers. (ii) The different levels of Social Networking Sites usage viz. high, average and low were not contributing significant effect on the Social Skills of the pupil teachers. (iii) The different levels of Social Skills viz. high and average level of the pupil teachers were contributing more positively towards the usage of Social Networking Sites. However, at low level of the social skill of the pupil teachers, this relationship was not significant.